A durable anti-mildew beauty glue with added reactive anti-mildew agent and preparation method thereof

By adding a reactive anti-mold agent to the beauty glue, the problem of insufficient anti-mold properties of the beauty glue in a high humidity and heat environment is solved, and durable anti-mold beauty glue with long-lasting anti-mold properties and a variety of excellent mechanical properties is prepared.

CN119144274BActive Publication Date: 2025-02-18SHANDONG YONGAN ADHESIVE IND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411613724.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing beauty glue is insufficient in high humidity and heat environments, which leads to the growth of mold and affects its application life.

Method used

The preparation method of adding a reactive anti-mold agent is adopted to prepare the reactive anti-mold agent through the steps of first-stage adsorption, second-stage adsorption, first-stage reaction and second-stage reaction, and mix it with the composite filler to form a durable anti-mold beauty gel.

Benefits of technology

The durable anti-mold beauty glue prepared not only has long-lasting anti-mold properties, but also maintains excellent adhesiveness, tensile strength, vibration resistance, weather resistance, temperature change resistance, stain resistance and moisture resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a durable mildew-proof beauty glue added with a reactive mildew-proof agent and a preparation method thereof, belonging to the technical field of beauty glue. The preparation method comprises the following steps: preparing a reactive mildew-proof agent, preparing a composite filler, and mixing materials; in the mixing, α,ω-dihydroxy polydimethylsiloxane, fumed silica, and dimethyl silicone oil are dispersed at high speed, the vacuum degree of the high-speed dispersion is controlled to be 0.090-0.095MPa, the rotation speed is 900-1000rpm, and after the high-speed dispersion is performed for 40-50min, methyltrimethoxysilane, the reactive mildew-proof agent, the composite filler, γ-aminopropyltriethoxysilane, and dibutyltin dilaurate are added, and the high-speed dispersion is continued for 60-70min; the durable mildew-proof beauty glue prepared by the invention not only has a durable mildew-proof property, but also has excellent adhesion, tensile strength, vibration resistance, weather resistance, temperature change resistance, antifouling and moisture resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cosmetic glue, and in particular to a durable anti-mildew cosmetic glue with a reactive anti-mildew agent added thereto and a preparation method thereof. Background Art

[0002] Beauty glue, also known as glass glue and silicone glue, is a material used to bond and seal various glasses to other substrates. Beauty glue is a paste made of polydimethylsiloxane as the main raw material, mixed with a cross-linking agent, a filler, a plasticizer, a coupling agent and a catalyst under a vacuum state. It undergoes a curing reaction at room temperature to form a network structure and release small molecules to form elastic silicone rubber. According to the type of small molecules released during the curing reaction, beauty glue is mainly divided into deacetic acid beauty glue, dealcohol beauty glue, deoxime beauty glue, etc.

[0003] Beauty glue has strong adhesion, high tensile strength, excellent moisture resistance, vibration resistance, weather resistance and temperature change resistance, and wide applicability. It can achieve adhesion between most building materials, so it has broad application prospects in the construction field. However, the beauty glue prepared with only polydimethylsiloxane, cross-linking agent, filler, plasticizer, coupling agent and catalyst as raw materials has poor mildew resistance. After the curing reaction occurs, the network structure formed has a porous structure. When used in high humidity and heat environments such as kitchens and bathrooms, the porous structure formed easily absorbs moisture, resulting in an increase in internal humidity, which provides conditions for the growth of mold. As time goes by, the moisture deteriorates and a large amount of mold is produced, resulting in the application of beauty glue in high humidity and heat environments such as kitchens and bathrooms being limited.

[0004] In order to improve the mildew resistance of the beauty glue, a common method is to add mildew inhibitors to the beauty glue to prepare mildew-proof beauty glue. Mildew inhibitors are mainly divided into organic mildew inhibitors and inorganic mildew inhibitors. Among them, the mildew-proof mechanism of organic mildew inhibitors is that when in contact with the cell wall of the mold, it fuses with the cell wall of the mold and gradually enters the mold cell, and inhibits the reproduction of the mold by interacting with the proteins and nucleic acids in the mold cell, thereby achieving mildew resistance; the mildew-proof mechanism of inorganic mildew inhibitors is that when in contact with mold bacteria, it destroys the bacterial wall, causing the mold to die, thereby achieving mildew resistance. However, organic mildew inhibitors have the disadvantage of a short duration of mildew resistance. Therefore, the mildew-proof beauty glue prepared by organic mildew inhibitors has the problem of a short duration of mildew resistance. Although the anti-mildew effect of inorganic mildew inhibitors lasts for a long time, the dispersibility of inorganic mildew inhibitors is poor and the compatibility with other ingredients of the anti-mildew beauty glue is poor, which will affect the network structure formed by the anti-mildew beauty glue after the curing reaction, further resulting in the anti-mildew beauty glue prepared with inorganic mildew inhibitors. The adhesion and tensile strength are reduced, and the vibration resistance, weather resistance and temperature change resistance are deteriorated.

[0005] In order to overcome the problems of organic mildew inhibitors and inorganic mildew inhibitors, one of the commonly used solutions is to use reactive mildew inhibitors. For reactive mildew inhibitors, the commonly used preparation method is to introduce mildew-proof groups into silane crosslinkers. When the curing reaction occurs, the silicon oxygen bonds in the reactive mildew inhibitor contact the moisture in the air and hydrolyze to obtain substances with active hydroxyl groups. The substances with active hydroxyl groups are cross-linked with the active groups in polydimethylsiloxane to obtain a network structure with mildew-proof groups. The mildew-proof effect of the mildew-proof beauty glue prepared by the reactive mildew inhibitor lasts for a long time, and because the mildew-proof groups have little effect on the curing reaction of the mildew-proof beauty glue and the formed network structure, it can also avoid the influence on the adhesion, tensile strength, vibration resistance, weather resistance and temperature change resistance of the mildew-proof beauty glue.

[0006] However, the mildew-proof beauty glue prepared by reactive mildew-proof agents still has the following deficiencies: First, due to the good mildew-proof and environmental protection properties of cationic quaternary ammonium groups, cationic quaternary ammonium groups are usually introduced into silane cross-linking agents as mildew-proof groups. However, in order to introduce mildew-proof groups while avoiding the influence on siloxane bonds, substances carrying mildew-proof groups are generally reacted with γ-glycidyloxypropyltrimethoxysilane, specifically reacting with the epoxy group of γ-glycidyloxypropyltrimethoxysilane under alkaline conditions. The activity of the epoxy group is large, so that the mildew-proof group is introduced while avoiding the influence on siloxane bonds. However, cationic quaternary ammonium groups are unstable under alkaline conditions, and the introduction process will affect the cationic quaternary ammonium groups, further resulting in a decrease in the mildew-proof property of the prepared mildew-proof beauty glue; second, cationic quaternary ammonium groups are easy to adsorb dust carrying anions in the air, resulting in poor antifouling properties of the prepared mildew-proof beauty glue; third, cationic quaternary ammonium groups are hydrophilic groups, which will lead to a decrease in moisture resistance of the mildew-proof beauty glue. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides a durable mildew-proof beauty glue with added reactive mildew inhibitor and a preparation method thereof. The prepared durable mildew-proof beauty glue not only has long-lasting mildew resistance, but also has excellent adhesion, tensile strength, vibration resistance, weather resistance, temperature change resistance, stain resistance and moisture resistance.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a durable anti-mildew beauty glue with a reactive anti-mildew agent added thereto comprises the following steps: preparing the reactive anti-mildew agent, preparing a composite filler, and mixing the materials;

[0010] The preparation of the reactive mildew inhibitor comprises the following steps: primary adsorption, secondary adsorption, primary reaction, and secondary reaction;

[0011] The first-level adsorption comprises adding montmorillonite and zinc nitrate aqueous solution into a reactor, controlling the stirring speed of the reactor to 200-400 rpm, stirring at room temperature for 3-3.5 hours, adding into a centrifuge, controlling the centrifugal speed of the centrifuge to 8000-9000 rpm, centrifuging for 10-12 minutes, taking a precipitate, washing the precipitate with deionized water, and drying to obtain a first-level adsorbent;

[0012] In the primary adsorption, the mass volume ratio of montmorillonite to the aqueous zinc nitrate solution is 100-120 g:1300-1500 mL;

[0013] The mass concentration of the zinc nitrate aqueous solution is 5%;

[0014] The particle size of the montmorillonite is 200 nm;

[0015] The secondary adsorption comprises adding the primary adsorbate and the tannic acid aqueous solution into a reactor, controlling the temperature of the reactor to 20-40° C., controlling the stirring speed to 200-400 rpm, stirring for 1-1.5 hours, adding the mixture into a centrifuge, controlling the centrifugal speed of the centrifuge to 8000-9000 rpm, centrifuging for 10-12 minutes, taking a precipitate, washing the precipitate with deionized water, and drying the precipitate to obtain a secondary adsorbate;

[0016] The mass volume ratio of the montmorillonite in the primary adsorption to the tannic acid aqueous solution in the secondary adsorption is 100-120 g:5400-5600 mL;

[0017] In the secondary adsorption, the mass concentration of the tannic acid aqueous solution is 10%;

[0018] The first-order reaction comprises adding the second-order adsorbent and the ethanol solution of octadecylamine into a reactor, controlling the temperature of the reactor to 35-45° C., controlling the stirring speed to 200-400 rpm, stirring for 4-5 hours, adding the reactor into a centrifuge, controlling the centrifugal speed of the centrifuge to 8000-9000 rpm, centrifuging for 10-12 minutes, taking a precipitate, washing the precipitate with anhydrous ethanol, and drying to obtain a first-order reactant;

[0019] The mass volume ratio of the montmorillonite in the primary adsorption to the ethanol solution of octadecylamine in the primary reaction is 100-120 g: 1700-2000 mL;

[0020] In the primary reaction, the mass concentration of the ethanol solution of octadecylamine is 0.5%;

[0021] The secondary reaction is as follows: adding the primary reactant, γ-glycidyloxypropyltrimethoxysilane and Tris-HCl buffer to a reactor, controlling the temperature of the reactor to 45-50°C, controlling the stirring speed to 200-400rpm, stirring for 2-2.5h, adding to a centrifuge, controlling the centrifugal speed of the centrifuge to 8000-9000rpm, centrifuging for 10-12min, taking a precipitate, washing the precipitate with deionized water, and drying to obtain a reactive mildew inhibitor;

[0022] The mass volume ratio of the montmorillonite in the primary adsorption to the γ-glycidyloxypropyltrimethoxysilane and Tris-HCl buffer in the secondary reaction is 100-120 g: 80-85 mL: 2000-2400 mL;

[0023] In the secondary reaction, the molar concentration of the Tris-HCl buffer is 0.05 mol / L and the pH is 8.5;

[0024] The preparation of the composite filler comprises the following steps: primary modification, secondary modification, tertiary modification, and quaternary modification;

[0025] The first-level modification comprises adding fumed silica and tannic acid aqueous solution into a reactor, controlling the stirring speed of the reactor to 400-500 rpm, stirring at room temperature for 30-40 min, adding an ultrasonic oscillator, controlling the frequency of the ultrasonic oscillator to 25-30 kHz, ultrasonically oscillating for 40-50 min, adding into a centrifuge, controlling the centrifugal speed of the centrifuge to 12000-13000 rpm, centrifuging for 14-16 min, taking a precipitate, washing the precipitate with deionized water, and drying to obtain a first-level modified product;

[0026] In the primary modification, the mass volume ratio of fumed silica to tannic acid aqueous solution is 140-150 g: 3000-3500 mL;

[0027] The mass concentration of the tannic acid aqueous solution is 10%;

[0028] The particle size of the fumed silica is 40 nm;

[0029] The secondary modification comprises adding the primary modification product and the zinc nitrate aqueous solution into a reaction kettle, controlling the stirring speed of the reaction kettle to 400-500 rpm, stirring at room temperature for 50-60 min, adding the primary modification product into a centrifuge, controlling the centrifugal speed of the centrifuge to 12000-13000 rpm, centrifuging for 14-16 min, taking a precipitate, washing the precipitate with deionized water, and drying to obtain a secondary modification product;

[0030] The mass volume ratio of the fumed silica in the primary modification to the zinc nitrate aqueous solution in the secondary modification is 140-150 g:3000-3500 mL;

[0031] In the secondary modification, the mass concentration of the zinc nitrate aqueous solution is 1%;

[0032] The tertiary modification comprises adding the secondary modification product, polydimethyldiallylammonium chloride aqueous solution and deionized water into a reaction kettle, controlling the stirring speed of the reaction kettle to 400-500 rpm, stirring at room temperature for 1-1.5 hours, adding the product into a centrifuge, controlling the centrifugal speed of the centrifuge to 12000-13000 rpm, centrifuging for 14-16 minutes, taking a precipitate, washing the precipitate with deionized water, and drying the product to obtain a tertiary modification product;

[0033] The mass volume ratio of the fumed silica in the primary modification to the polydimethyldiallylammonium chloride aqueous solution and deionized water in the tertiary modification is 140-150 g: 200-220 mL: 2500-3000 mL;

[0034] In the three-stage modification, the mass concentration of the polydimethyldiallylammonium chloride aqueous solution is 40%;

[0035] The four-stage modification is to add the ethanol solution of the three-stage modification product and the block polyether F-68 into a reactor, control the stirring speed of the reactor to 400-500 rpm, stir at room temperature for 1-1.5 hours, add into a centrifuge, control the centrifugal speed of the centrifuge to 12000-13000 rpm, centrifuge for 14-16 minutes, take the precipitate, wash the precipitate with anhydrous ethanol, and dry to obtain a composite filler;

[0036] The mass volume ratio of the fumed silica in the primary modification to the ethanol solution of the block polyether F-68 in the quadruple modification is 140-150 g: 5000-5500 mL;

[0037] In the four-stage modification, the mass concentration of the ethanol solution of the block polyether F-68 is 2%;

[0038] The mixing material is added into a high-speed disperser, wherein the vacuum degree of the high-speed disperser is controlled to 0.090-0.095 MPa, the rotation speed is controlled to 900-1000 rpm, and after high-speed dispersion for 40-50 minutes, methyl trimethoxy silane, reactive mildew inhibitor, composite filler, γ-aminopropyl triethoxy silane, and dibutyl tin dilaurate are added, and high-speed dispersion is continued for 60-70 minutes to obtain a durable mildew-proof beauty glue;

[0039] In the mixture, the mass ratio of α,ω-dihydroxy polydimethylsiloxane, fumed silica, dimethyl silicone oil, methyl trimethoxy silane, reactive mildew inhibitor, composite filler, γ-aminopropyl triethoxy silane and dibutyl tin dilaurate is 380-400:55-60:40-45:27-30:20-25:18-20:7-9:3.3-3.5;

[0040] The viscosity of the α,ω-dihydroxy polydimethylsiloxane at 25° C. is 80000 mPa·s;

[0041] The particle size of the fumed silica is 40 nm;

[0042] The viscosity of the dimethyl silicone oil at 25° C. is 500 mPa·s.

[0043] A durable anti-mildew beauty glue with a reactive anti-mildew agent added, which is prepared by the above-mentioned preparation method.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] (1) The method for preparing a durable anti-mildew beauty glue with a reactive anti-mildew agent added to the present invention comprises preparing a reactive anti-mildew agent and a composite filler respectively. The method for preparing the reactive anti-mildew agent comprises a primary adsorption, a secondary adsorption, a primary reaction, and a secondary reaction. The primary adsorption comprises soaking montmorillonite with an aqueous solution of zinc nitrate, adsorbing zinc ions on the surface and between layers of the montmorillonite, and obtaining a primary adsorbate. The secondary adsorption comprises soaking the primary adsorbate with an aqueous solution of tannic acid, adsorbing tannic acid on the surface and between layers of the primary adsorbate, and obtaining a secondary adsorbate. The primary reaction comprises reacting octadecylamine with the surface of the secondary adsorbate and part of the tannic acid on the surface, introducing octadecyl groups, and obtaining to the primary reactant; the secondary reaction is to use γ-glycidyloxypropyltrimethoxysilane to react with the residual tannic acid on the surface and between the layers of the primary reactant to obtain a reactive mildew inhibitor; the purpose of the primary adsorption is to improve the mildew resistance of the montmorillonite by adsorbing zinc ions on the surface and between the layers of the montmorillonite, and on the other hand, through the coordination effect between zinc ions and tannic acid, thereby increasing the adsorption force and adsorption amount of tannic acid in the secondary adsorption, reducing the adsorption of dust in the air by the montmorillonite, thereby improving the long-lasting mildew resistance and antifouling properties of the prepared durable mildew-proof beauty glue; the purpose of the primary reaction is to introduce octadecyl through the reaction of octadecylamine with the hydroxyl group of tannic acid, thereby improving The hydrophobicity of the primary reactant and the dispersibility of the reactive mildew inhibitor improve the adhesion, tensile strength, vibration resistance, weather resistance, temperature change resistance and moisture resistance of the prepared durable mildew-proof beauty glue. The purpose of the secondary reaction is to obtain a reactive mildew inhibitor having a hydrophobic group and a cross-linkable siloxy bond through the reaction of γ-glycidyloxypropyltrimethoxysilane with the hydroxyl group of tannic acid. In addition, the reactive mildew inhibitor with a mildew-proof group can cross-link with the surface and interlayer siloxy bonds of the reactive mildew inhibitor during the curing reaction of the durable mildew-proof beauty glue. The reactive mildew inhibitor plays the role of a cross-linking point and can also increase the density of the network structure formed after the curing reaction; the composite filler The preparation method comprises primary modification, secondary modification, tertiary modification and quaternary modification, wherein the primary modification is to coat fumed silica with tannic acid to obtain a primary modification; the secondary modification is to impregnate the primary modification with a zinc nitrate aqueous solution, and introduce zinc ions through the coordination effect of tannic acid and zinc ions; the tertiary modification is to impregnate the secondary modification with a polydimethyldiallylammonium chloride aqueous solution, and polydimethyldiallylammonium chloride, zinc ions and tannic acid form a supramolecule with mildew resistance through intermolecular forces, wherein the zinc ions play a bridging role, so they are added between tannic acid and polydimethyldiallylammonium chloride;The fourth-level modification is to use an ethanol solution of block polyether F-68 to impregnate the third-level modification. The polyoxyethylene segment in the block polyether F-68 has an intermolecular force with the supramolecule with mildew resistance, thereby firmly bonding to the surface of the third-level modification, and playing a fixing and coating role on the supramolecule with mildew resistance. The polyoxypropylene segment in the block polyether F-68 is on the outermost side, and the polyoxypropylene segment is hydrophobic, thereby playing a hydrophobic role and improving the dispersibility of the composite filler. The supramolecule formed by combining tannic acid, zinc ions, polydimethyldiallylammonium chloride, and the polyoxyethylene segment in the block polyether F-68 can adsorb and kill mold, thereby improving the long-lasting mildew resistance, adhesion, tensile strength, vibration resistance, weather resistance, temperature change resistance, antifouling property, and moisture resistance of the prepared durable mildew-proof beauty glue.

[0046] (2) The method for preparing a durable mildew-proof cosmetic glue with an added reactive mildew-proof agent of the present invention, wherein the prepared durable mildew-proof cosmetic glue has a long-lasting mildew-proof property. The test is carried out according to the GB / T 1741-2020 test standard. The test strain is Aspergillus niger. The culture time is 7 days. The mildew-proof grade is 0 (no growth). On the basis of the GB / T 1741-2020 test standard, the culture time is extended to 100 days. The mildew-proof grade is still not 0 (no growth).

[0047] (3) The method for preparing a durable mildew-proof beauty glue with a reactive mildew-proof agent added according to the present invention, wherein the prepared durable mildew-proof beauty glue has excellent bonding strength. According to the test standard GB / T16776-2005, the tensile bonding strength at 23°C is 3.15-3.23MPa, and the bonding failure area is 0%;

[0048] (4) The method for preparing the durable mildew-proof beauty glue with added reactive mildew-proof agent of the present invention, wherein the prepared durable mildew-proof beauty glue has excellent tensile strength. The tensile strength is 2.88-2.97 MPa when tested according to the GB / T528-2009 test standard;

[0049] (5) The method for preparing a durable mildew-proof beauty glue with a reactive mildew-proof agent added according to the present invention, wherein the prepared durable mildew-proof beauty glue has excellent vibration resistance. When tested according to the GB / T13477-2017 test standard, the elongation at break is 448-461%, and when tested according to the GB / T14683-2017 test standard, the elastic recovery rate is 92-94%;

[0050] (6) The method for preparing a durable mildew-proof beauty glue with a reactive mildew-proof agent added according to the present invention, wherein the prepared durable mildew-proof beauty glue has excellent weather resistance. The durable mildew-proof beauty glue prepared according to the present invention is subjected to ultraviolet irradiation in an environment of 23°C, and the wavelength of the ultraviolet light is controlled to be 250nm. After continuous irradiation for 30 days, the tensile strength decrease rate is 0-0.68%, the elongation at break decrease rate is 1.23-1.87%, and the elastic recovery rate decrease rate is 0-1.10%;

[0051] (7) The method for preparing a durable mildew-proof beauty glue with a reactive mildew-proof agent added according to the present invention, wherein the prepared durable mildew-proof beauty glue has excellent resistance to temperature changes. The durable mildew-proof beauty glue prepared according to the present invention is placed in an environment of 60°C for 10 days, then cooled to -40°C at a cooling rate of 5°C / min, and placed in an environment of -40°C for 10 days. The decrease rate of tensile strength is 1.37-1.82%, the decrease rate of elongation at break is 2.68-3.26%, and the decrease rate of elastic recovery rate is 1.06-2.17%;

[0052] (8) The method for preparing a durable mildew-proof beauty glue with a reactive mildew-proof agent added according to the present invention, wherein the prepared durable mildew-proof beauty glue has excellent antifouling properties, and the durable mildew-proof beauty glue prepared according to the present invention is injected into a mold with a specification of 50 mm×50 mm×2 mm, and after the mold is completely filled, it is naturally cured in an outdoor environment for 30 days, and the number of dust particles on the surface is 0≤≤10;

[0053] (9) The method for preparing a durable mildew-proof beauty glue with a reactive mildew-proof agent added thereto according to the present invention has excellent moisture resistance. The durable mildew-proof beauty glue prepared by the present invention is made into a film with a thickness of 2 mm. After being completely cured, the water vapor transmission rate at 23°C is 4.9-5.4 g / (m 2 ·24h). DETAILED DESCRIPTION

[0054] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0055] Example 1

[0056] A method for preparing a durable anti-mildew beauty glue with an added reactive anti-mildew agent, specifically comprising:

[0057] 1. Preparation of reactive mildew inhibitor:

[0058] (1) Primary adsorption: 100 g of montmorillonite and 1300 mL of 5% zinc nitrate aqueous solution were added to a reactor, the stirring speed of the reactor was controlled to 200 rpm, and the mixture was stirred at room temperature for 3 h. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 8000 rpm, and the mixture was centrifuged for 10 min. The precipitate was collected, washed with deionized water, and dried to obtain a primary adsorbent.

[0059] The particle size of the montmorillonite is 200 nm;

[0060] (2) Secondary adsorption: The primary adsorbate obtained in the primary adsorption of step (1) and 5400 mL of 10% mass concentration tannic acid aqueous solution are added to a reactor, the temperature of the reactor is controlled to 20°C, the stirring speed is controlled to 200 rpm, and the stirring is performed for 1 hour. The mixture is added to a centrifuge, the centrifugal speed of the centrifuge is controlled to 8000 rpm, and the mixture is centrifuged for 10 minutes. The precipitate is collected, washed with deionized water, and dried to obtain a secondary adsorbate.

[0061] (3) Primary reaction: add the secondary adsorbate obtained in the secondary adsorption in step (2) and 1700 mL of 0.5% octadecylamine ethanol solution into a reactor, control the temperature of the reactor to 35°C, control the stirring speed to 200 rpm, stir for 4 h, add into a centrifuge, control the centrifugal speed to 8000 rpm, centrifuge for 10 min, take the precipitate, wash the precipitate with anhydrous ethanol, dry, and obtain the primary reactant;

[0062] (4) Secondary reaction: Add the primary reactant obtained in the primary reaction of step (3), 80 mL of γ-glycidyloxypropyltrimethoxysilane, and 2000 mL of Tris-HCl buffer into a reactor, control the temperature of the reactor to 45°C, control the stirring speed to 200 rpm, stir for 2 h, add to a centrifuge, control the centrifugal speed of the centrifuge to 8000 rpm, centrifuge for 10 min, take the precipitate, wash the precipitate with deionized water, and dry to obtain a reactive mildew inhibitor;

[0063] The molar concentration of the Tris-HCl buffer is 0.05 mol / L, and the pH is 8.5;

[0064] 2. Preparation of composite fillers:

[0065] (1) Primary modification: 140 g of fumed silica and 3000 mL of 10% tannic acid aqueous solution were added to a reactor, the stirring speed of the reactor was controlled to 400 rpm, and the mixture was stirred at room temperature for 30 min. An ultrasonic oscillator was added, and the frequency of the ultrasonic oscillator was controlled to 25 kHz. The mixture was ultrasonically oscillated for 40 min. The mixture was added to a centrifuge, and the centrifugal speed of the centrifuge was controlled to 12000 rpm. The mixture was centrifuged for 14 min. The precipitate was collected and washed with deionized water and dried to obtain a primary modified product.

[0066] The particle size of the fumed silica is 40 nm;

[0067] (2) Secondary modification: The primary modification product obtained in the primary modification of step (1) and 3000 mL of a 1% zinc nitrate aqueous solution were added to a reactor, the stirring speed of the reactor was controlled to 400 rpm, and the mixture was stirred at room temperature for 50 min. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 12000 rpm, and the mixture was centrifuged for 14 min. The precipitate was collected, washed with deionized water, and dried to obtain a secondary modification product.

[0068] (3) Tertiary modification: The secondary modification product obtained in the secondary modification in step (2), 200 mL of a 40% polydimethyldiallyl ammonium chloride aqueous solution, and 2500 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 400 rpm, and the mixture was stirred at room temperature for 1 h. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 12000 rpm, and the mixture was centrifuged for 14 min. The precipitate was collected, washed with deionized water, and dried to obtain a tertiary modification product.

[0069] (4) Quaternary modification: add the tertiary modified product obtained in the secondary modification in step (3) and 5000 mL of ethanol solution of block polyether F-68 with a mass concentration of 2% into a reactor, control the stirring speed of the reactor to 400 rpm, stir at room temperature for 1 hour, add into a centrifuge, control the centrifugal speed of the centrifuge to 12000 rpm, centrifuge for 14 minutes, take out the precipitate, wash the precipitate with anhydrous ethanol, and dry to obtain a composite filler;

[0070] 3. Mixing: Add 380g α,ω-dihydroxy polydimethylsiloxane (107 base glue), 55g fumed silica, and 40g dimethyl silicone oil into a high-speed disperser, control the vacuum degree of the high-speed disperser to 0.090MPa, and the speed to 900rpm. After high-speed dispersion for 40min, add 27g methyltrimethoxysilane, 20g reactive mildew inhibitor, 18g composite filler, 7g γ-aminopropyltriethoxysilane, and 3.3g dibutyltin dilaurate, and continue high-speed dispersion for 60min to obtain a durable mildew-proof beauty glue;

[0071] The viscosity of the α,ω-dihydroxy polydimethylsiloxane at 25° C. is 80000 mPa·s;

[0072] The particle size of the fumed silica is 40 nm;

[0073] The viscosity of the dimethyl silicone oil at 25° C. is 500 mPa·s.

[0074] This embodiment also provides a durable anti-mildew beauty glue with added reactive anti-mildew agent prepared by the aforementioned preparation method.

[0075] Example 2

[0076] A method for preparing a durable anti-mildew beauty glue with an added reactive anti-mildew agent, specifically comprising:

[0077] 1. Preparation of reactive mildew inhibitor:

[0078] (1) Primary adsorption: 110 g of montmorillonite and 1400 mL of 5% zinc nitrate aqueous solution were added to a reactor, the stirring speed of the reactor was controlled to 300 rpm, and the mixture was stirred at room temperature for 3.5 h. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 8500 rpm, and the mixture was centrifuged for 11 min. The precipitate was collected, washed with deionized water, and dried to obtain a primary adsorbent.

[0079] The particle size of the montmorillonite is 200 nm;

[0080] (2) Secondary adsorption: The primary adsorbate obtained in the primary adsorption of step (1) and 5500 mL of 10% mass concentration tannic acid aqueous solution were added to a reactor, the temperature of the reactor was controlled to 30°C, the stirring speed was controlled to 300 rpm, and the stirring was performed for 1.5 h. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 8500 rpm, and the mixture was centrifuged for 11 min. The precipitate was collected, washed with deionized water, and dried to obtain a secondary adsorbate.

[0081] (3) Primary reaction: add the secondary adsorbate obtained in the secondary adsorption in step (2) and 1800 mL of 0.5% octadecylamine ethanol solution into a reactor, control the temperature of the reactor to 40°C, control the stirring speed to 300 rpm, stir for 4.5 h, add into a centrifuge, control the centrifugal speed to 8500 rpm, centrifuge for 11 min, take the precipitate, wash the precipitate with anhydrous ethanol, dry, and obtain the primary reactant;

[0082] (4) Secondary reaction: Add the primary reactant obtained in the primary reaction of step (3), 82 mL of γ-glycidyloxypropyltrimethoxysilane, and 2200 mL of Tris-HCl buffer into a reactor, control the temperature of the reactor to 48°C, control the stirring speed to 400 rpm, stir for 2.5 hours, add to a centrifuge, control the centrifugal speed of the centrifuge to 8500 rpm, centrifuge for 11 minutes, take the precipitate, wash the precipitate with deionized water, and dry to obtain a reactive mildew inhibitor;

[0083] The molar concentration of the Tris-HCl buffer is 0.05 mol / L, and the pH is 8.5;

[0084] 2. Preparation of composite fillers:

[0085] (1) Primary modification: 145 g of fumed silica and 3200 mL of 10% tannic acid aqueous solution were added to a reactor, the stirring speed of the reactor was controlled to 450 rpm, and the mixture was stirred at room temperature for 35 min. An ultrasonic oscillator was added, and the frequency of the ultrasonic oscillator was controlled to 30 kHz. The mixture was ultrasonically oscillated for 45 min. The mixture was added to a centrifuge, and the centrifugal speed of the centrifuge was controlled to 13000 rpm. The mixture was centrifuged for 15 min. The precipitate was collected and washed with deionized water and dried to obtain a primary modified product.

[0086] The particle size of the fumed silica is 40 nm;

[0087] (2) Secondary modification: The primary modification product obtained in the primary modification of step (1) and 3200 mL of a 1% zinc nitrate aqueous solution were added to a reactor, the stirring speed of the reactor was controlled to 450 rpm, and the mixture was stirred at room temperature for 55 min. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 13000 rpm, and the mixture was centrifuged for 15 min. The precipitate was collected, washed with deionized water, and dried to obtain a secondary modification product.

[0088] (3) Tertiary modification: The secondary modification product obtained in the secondary modification in step (2), 210 mL of a 40% polydimethyldiallyl ammonium chloride aqueous solution, and 2800 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 450 rpm, and the mixture was stirred at room temperature for 1.5 h. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 13000 rpm, and the mixture was centrifuged for 15 min. The precipitate was collected, washed with deionized water, and dried to obtain a tertiary modification product.

[0089] (4) Quaternary modification: add the tertiary modified product obtained in the secondary modification in step (3) and 5200 mL of ethanol solution of block polyether F-68 with a mass concentration of 2% into the reactor, control the stirring speed of the reactor to 450 rpm, stir at room temperature for 1.5 h, add into the centrifuge, control the centrifugal speed of the centrifuge to 13000 rpm, centrifuge for 15 min, take the precipitate, wash the precipitate with anhydrous ethanol, and dry to obtain the composite filler;

[0090] 3. Mixing: Add 390g α,ω-dihydroxy polydimethylsiloxane (107 base glue), 58g fumed silica, and 42g dimethyl silicone oil into a high-speed disperser, control the vacuum degree of the high-speed disperser to 0.092MPa, and the speed to 950rpm. After high-speed dispersion for 45 minutes, add 29g methyltrimethoxysilane, 22g reactive mildew inhibitor, 19g composite filler, 8g γ-aminopropyltriethoxysilane, and 3.4g dibutyltin dilaurate, and continue high-speed dispersion for 65 minutes to obtain a durable mildew-proof beauty glue;

[0091] The viscosity of the α,ω-dihydroxy polydimethylsiloxane at 25° C. is 80000 mPa·s;

[0092] The particle size of the fumed silica is 40 nm;

[0093] The viscosity of the dimethyl silicone oil at 25° C. is 500 mPa·s.

[0094] This embodiment also provides a durable anti-mildew beauty glue with added reactive anti-mildew agent prepared by the aforementioned preparation method.

[0095] Example 3

[0096] A method for preparing a durable anti-mildew beauty glue with an added reactive anti-mildew agent, specifically comprising:

[0097] 1. Preparation of reactive mildew inhibitor:

[0098] (1) Primary adsorption: 120 g of montmorillonite and 1500 mL of 5% zinc nitrate aqueous solution were added to a reactor, the stirring speed of the reactor was controlled to 400 rpm, and the mixture was stirred at room temperature for 3.5 h. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 9000 rpm, and the mixture was centrifuged for 12 min. The precipitate was collected, washed with deionized water, and dried to obtain a primary adsorbent.

[0099] The particle size of the montmorillonite is 200 nm;

[0100] (2) Secondary adsorption: The primary adsorbate obtained in the primary adsorption of step (1) and 5600 mL of 10% mass concentration tannic acid aqueous solution were added to a reactor, the temperature of the reactor was controlled to 40°C, the stirring speed was controlled to 400 rpm, and the stirring was performed for 1.5 h. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 9000 rpm, and the mixture was centrifuged for 12 min. The precipitate was collected, washed with deionized water, and dried to obtain a secondary adsorbate.

[0101] (3) Primary reaction: add the secondary adsorbate obtained in the secondary adsorption in step (2) and 2000 mL of 0.5% octadecylamine ethanol solution into a reactor, control the temperature of the reactor to 45°C, control the stirring speed to 400 rpm, stir for 5 h, add into a centrifuge, control the centrifugal speed to 9000 rpm, centrifuge for 12 min, take the precipitate, wash the precipitate with anhydrous ethanol, dry, and obtain the primary reactant;

[0102] (4) Secondary reaction: Add the primary reactant obtained in the primary reaction of step (3), 85 mL of γ-glycidyloxypropyltrimethoxysilane, and 2400 mL of Tris-HCl buffer into a reactor, control the temperature of the reactor to 50°C, control the stirring speed to 400 rpm, stir for 2.5 hours, add to a centrifuge, control the centrifugal speed of the centrifuge to 9000 rpm, centrifuge for 12 minutes, take the precipitate, wash the precipitate with deionized water, and dry to obtain a reactive mildew inhibitor;

[0103] The molar concentration of the Tris-HCl buffer is 0.05 mol / L, and the pH is 8.5;

[0104] 2. Preparation of composite fillers:

[0105] (1) Primary modification: 150 g of fumed silica and 3500 mL of 10% tannic acid aqueous solution were added to a reactor, the stirring speed of the reactor was controlled to 500 rpm, and the mixture was stirred at room temperature for 40 min. An ultrasonic oscillator was added, and the frequency of the ultrasonic oscillator was controlled to 30 kHz. The mixture was ultrasonically oscillated for 50 min. The mixture was added to a centrifuge, and the centrifugal speed of the centrifuge was controlled to 13000 rpm. The mixture was centrifuged for 16 min. The precipitate was collected and washed with deionized water and dried to obtain a primary modified product.

[0106] The particle size of the fumed silica is 40 nm;

[0107] (2) Secondary modification: The primary modification product obtained in the primary modification of step (1) and 3500 mL of a 1% zinc nitrate aqueous solution were added to a reactor, the stirring speed of the reactor was controlled to 500 rpm, and the mixture was stirred at room temperature for 60 min. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 13000 rpm, and the mixture was centrifuged for 16 min. The precipitate was collected, washed with deionized water, and dried to obtain a secondary modification product.

[0108] (3) Tertiary modification: The secondary modification product obtained in the secondary modification in step (2), 220 mL of a 40% polydimethyldiallyl ammonium chloride aqueous solution, and 3000 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 500 rpm, and the mixture was stirred at room temperature for 1.5 h. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 13000 rpm, and the mixture was centrifuged for 16 min. The precipitate was collected, washed with deionized water, and dried to obtain a tertiary modification product.

[0109] (4) Quaternary modification: add the tertiary modified product obtained in the secondary modification in step (3) and 5500 mL of ethanol solution of block polyether F-68 with a mass concentration of 2% into the reactor, control the stirring speed of the reactor to 500 rpm, stir at room temperature for 1.5 h, add into the centrifuge, control the centrifugal speed of the centrifuge to 13000 rpm, centrifuge for 16 min, take the precipitate, wash the precipitate with anhydrous ethanol, and dry to obtain the composite filler;

[0110] 3. Mixing: Add 400g α,ω-dihydroxy polydimethylsiloxane (107 base glue), 60g fumed silica, and 45g dimethyl silicone oil into a high-speed disperser, control the vacuum degree of the high-speed disperser to 0.095MPa, and the speed to 1000rpm. After high-speed dispersion for 50min, add 30g methyltrimethoxysilane, 25g reactive mildew inhibitor, 20g composite filler, 9g γ-aminopropyltriethoxysilane, and 3.5g dibutyltin dilaurate, and continue high-speed dispersion for 70min to obtain a durable mildew-proof beauty glue;

[0111] The viscosity of the α,ω-dihydroxy polydimethylsiloxane at 25° C. is 80000 mPa·s;

[0112] The particle size of the fumed silica is 40 nm;

[0113] The viscosity of the dimethyl silicone oil at 25° C. is 500 mPa·s.

[0114] This embodiment also provides a durable anti-mildew beauty glue with added reactive anti-mildew agent prepared by the aforementioned preparation method.

[0115] Comparative Example 1

[0116] On the basis of Example 2, in the step 1 of preparing the reactive mildew inhibitor, the first-order adsorption step (1) and the first-order reaction step (3) are omitted. Accordingly, the first step of preparing the reactive mildew inhibitor is specifically changed to:

[0117] (1) Adsorption: 110 g of montmorillonite and 5500 mL of 10% tannic acid aqueous solution were added to a reactor, the temperature of the reactor was controlled to 30 ° C, the stirring speed was controlled to 300 rpm, and the stirring was performed for 1.5 h. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 8500 rpm, and the mixture was centrifuged for 11 min. The precipitate was collected and washed with deionized water, and then dried to obtain an adsorbate.

[0118] The particle size of the montmorillonite is 200 nm;

[0119] (2) Reaction: Add the adsorbate obtained in step (1), 82 mL of γ-glycidyloxypropyltrimethoxysilane, and 2200 mL of Tris-HCl buffer into a reactor, control the temperature of the reactor to 48°C, control the stirring speed to 400 rpm, stir for 2.5 hours, add to a centrifuge, control the centrifugal speed of the centrifuge to 8500 rpm, centrifuge for 11 minutes, take the precipitate, wash the precipitate with deionized water, and dry to obtain a reactive mildew inhibitor;

[0120] The molar concentration of the Tris-HCl buffer is 0.05 mol / L, and the pH is 8.5.

[0121] The rest of the technical solutions are the same as those in Example 2.

[0122] Comparative Example 2

[0123] On the basis of Example 2, in the second step of preparing the composite filler, the first-level modification step (1) and the fourth-level modification step (4) are omitted. Accordingly, the second step of preparing the composite filler is specifically changed to:

[0124] (1) Primary modification: 145 g of fumed silica and 3200 mL of a 1% aqueous zinc nitrate solution were added to a reactor, the stirring speed of the reactor was controlled to 450 rpm, and the mixture was stirred at room temperature for 55 min. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 13000 rpm, and the mixture was centrifuged for 15 min. The precipitate was collected, washed with deionized water, and dried to obtain a primary modified product.

[0125] The particle size of the fumed silica is 40 nm;

[0126] (2) Secondary modification: The primary modification product obtained in the primary modification of step (1), 210 mL of a 40% polydimethyldiallylammonium chloride aqueous solution, and 2800 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 450 rpm, and the mixture was stirred at room temperature for 1.5 h. The mixture was added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 13,000 rpm, and the mixture was centrifuged for 15 min. The precipitate was collected, washed with deionized water, and dried to obtain a composite filler.

[0127] Test Example 1

[0128] The mildew resistance grade, tensile adhesion, tensile strength, elongation at break, and elastic recovery rate of the durable mildew resistance cosmetic glue prepared in Examples 1-3 and Comparative Examples 1-2 were sampled and tested, and the test results are as follows:

[0129]

[0130] Test Example 2

[0131] The durable mildew resistance of the durable mildew-proof beauty glue prepared in Examples 1-3 and Comparative Examples 1-2 was tested. Specifically, after sampling, the test was carried out according to the GB / T 1741-2020 test standard, using Aspergillus niger as the test strain, but the test time (i.e., the culture time after inoculating Aspergillus niger on the surface of the sample) was extended from 7 days to 100 days, and then the growth of Aspergillus niger on the surface of the sample was observed and rated. The rating results are as follows:

[0132]

[0133] Test Example 3

[0134] After sampling the durable mildew-proof beauty glue prepared in Examples 1-3 and Comparative Examples 1-2, the tensile strength, elongation at break, and elastic recovery rate of the test samples were tested, and then the test samples were irradiated with ultraviolet light in an environment of 23°C, and the wavelength of the ultraviolet light was controlled to be 250nm. After continuous irradiation for 30 days, the tensile strength, elongation at break, and elastic recovery rate of the test samples were tested, and the tensile strength decrease rate, elongation at break decrease rate, and elastic recovery rate decrease rate were calculated. The calculation results are as follows:

[0135]

[0136] Test Example 4

[0137] After sampling the durable mildew-proof beauty glue prepared in Examples 1-3 and Comparative Examples 1-2, the tensile strength, elongation at break, and elastic recovery rate of the test samples were tested, and then the test samples were allowed to stand for 10 days in an environment at 60°C, and then cooled to -40°C at a cooling rate of 5°C / min, and allowed to stand for 10 days in an environment at -40°C, and then the tensile strength, elongation at break, and elastic recovery rate of the test samples were tested, and the tensile strength decrease rate, elongation at break decrease rate, and elastic recovery rate decrease rate were calculated, and the calculation results are as follows:

[0138]

[0139] Test Example 5

[0140] The durable mildew-proof cosmetic glues prepared in Examples 1-3 and Comparative Examples 1-2 were respectively injected into molds with a specification of 50 mm×50 mm×2 mm. After the molds were completely filled, they were naturally cured for 30 days in the same outdoor environment. Then, the number of dust particles on the surface was observed and recorded. The anti-pollution effect was evaluated according to the number of dust particles on the surface. The evaluation criteria were as follows:

[0141] 0≤Number of surface dust particles≤10: Very good

[0142] 10<Number of dust particles on the surface≤20: Good

[0143] 20<The number of dust particles on the surface≤30: General

[0144] 30<Number of dust particles on the surface≤40: Poor

[0145] 40<The number of dust particles on the surface: Very poor

[0146] The evaluation results are as follows:

[0147]

[0148] Test Example 6

[0149] The durable mildew-proof beauty glue prepared in Example 1-3 and Comparative Example 1-2 was made into a 2 mm thick film. After being completely cured, the water vapor transmission rate of the film was tested at 23°C. The test results are as follows:

[0150]

[0151] It can be seen from the results of Test Examples 1-6 that the durable mildew-proof beauty glue prepared in Comparative Examples 1-2 is inferior to the durable mildew-proof beauty glue prepared in Example 2 in terms of long-lasting mildew-proofness, adhesion, tensile strength, vibration resistance, weather resistance, temperature change resistance, stain resistance and moisture resistance.

[0152] Unless otherwise specified, all percentages used in the present invention are by mass.

[0153] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a durable anti-mildew beauty glue with an added reactive anti-mildew agent, characterized in that: The method comprises the following steps: preparing a reactive mildew inhibitor, preparing a composite filler, and mixing materials; The preparation of the reactive mildew inhibitor comprises the following steps: primary adsorption, secondary adsorption, primary reaction, and secondary reaction; The first-stage adsorption comprises mixing montmorillonite and an aqueous solution of zinc nitrate, stirring at room temperature, centrifuging, taking a precipitate, washing the precipitate and drying it to obtain a first-stage adsorbent; In the primary adsorption, the mass volume ratio of montmorillonite to the aqueous zinc nitrate solution is 100-120 g:1300-1500 mL; The mass concentration of the zinc nitrate aqueous solution is 5%; The secondary adsorption comprises mixing the primary adsorbate and the tannic acid aqueous solution, stirring at 20-40° C., centrifuging, taking a precipitate, washing the precipitate and drying it to obtain a secondary adsorbate; The mass volume ratio of the montmorillonite in the primary adsorption to the tannic acid aqueous solution in the secondary adsorption is 100-120 g:5400-5600 mL; In the secondary adsorption, the mass concentration of the tannic acid aqueous solution is 10%; In the first-order reaction, the second-order adsorbent and the ethanol solution of octadecylamine are mixed, stirred at 35-45° C., centrifuged, a precipitate is taken, the precipitate is washed and dried to obtain a first-order reactant; The mass volume ratio of the montmorillonite in the primary adsorption to the ethanol solution of octadecylamine in the primary reaction is 100-120 g: 1700-2000 mL; In the primary reaction, the mass concentration of the ethanol solution of octadecylamine is 0.5%; The secondary reaction comprises mixing the primary reactant, γ-glycidyloxypropyltrimethoxysilane and Tris-HCl buffer, stirring at 45-50° C., centrifuging, taking a precipitate, washing the precipitate and drying it to obtain a reactive mildew inhibitor; The mass volume ratio of the montmorillonite in the primary adsorption to the γ-glycidyloxypropyltrimethoxysilane and Tris-HCl buffer in the secondary reaction is 100-120 g: 80-85 mL: 2000-2400 mL; In the secondary reaction, the molar concentration of the Tris-HCl buffer is 0.05 mol / L and the pH is 8.5; The preparation of the composite filler comprises the following steps: primary modification, secondary modification, tertiary modification, and quaternary modification; The first-stage modification comprises mixing fumed silica and tannic acid aqueous solution, stirring at room temperature, ultrasonically shaking, centrifuging, taking a precipitate, washing the precipitate and drying it to obtain a first-stage modified product; In the primary modification, the mass volume ratio of fumed silica to tannic acid aqueous solution is 140-150 g: 3000-3500 mL; The mass concentration of the tannic acid aqueous solution is 10%; The secondary modification comprises mixing the primary modification product and a zinc nitrate aqueous solution, stirring at room temperature, centrifuging, taking a precipitate, washing the precipitate and drying it to obtain a secondary modification product; The mass volume ratio of the fumed silica in the primary modification to the zinc nitrate aqueous solution in the secondary modification is 140-150 g:3000-3500 mL; In the secondary modification, the mass concentration of the zinc nitrate aqueous solution is 1%; The tertiary modification comprises mixing the secondary modification product, polydimethyldiallyl ammonium chloride aqueous solution and deionized water, stirring at room temperature, centrifuging, taking a precipitate, washing the precipitate and drying it to obtain a tertiary modification product; The mass volume ratio of the fumed silica in the primary modification to the polydimethyldiallylammonium chloride aqueous solution and deionized water in the tertiary modification is 140-150 g: 200-220 mL: 2500-3000 mL; In the three-stage modification, the mass concentration of the polydimethyldiallylammonium chloride aqueous solution is 40%; The four-stage modification comprises mixing the three-stage modification product and the ethanol solution of the block polyether F-68, stirring at room temperature, centrifuging, taking a precipitate, washing the precipitate and drying it to obtain a composite filler; The mass volume ratio of the fumed silica in the primary modification to the ethanol solution of the block polyether F-68 in the quadruple modification is 140-150 g: 5000-5500 mL; In the four-stage modification, the mass concentration of the ethanol solution of the block polyether F-68 is 2%; The mixing material is high-speed dispersed with α,ω-dihydroxy polydimethylsiloxane, fumed silica and dimethyl silicone oil, the vacuum degree of high-speed dispersion is controlled to be 0.090-0.095MPa, the rotation speed is 900-1000rpm, after high-speed dispersion for 40-50min, methyltrimethoxysilane, reactive mildew inhibitor, composite filler, γ-aminopropyltriethoxysilane and dibutyltin dilaurate are added, and high-speed dispersion is continued for 60-70min to obtain a durable mildew-proof beauty glue; In the mixture, the mass ratio of α,ω-dihydroxypolydimethylsiloxane, fumed silica, dimethyl silicone oil, methyltrimethoxysilane, reactive mildew inhibitor, composite filler, γ-aminopropyltriethoxysilane and dibutyltin dilaurate is 380-400:55-60:40-45:27-30:20-25:18-20:7-9:3.3-3.

5.

2. The method for preparing the durable anti-mildew beauty glue with added reactive anti-mildew agent according to claim 1, characterized in that: In the primary adsorption, the particle size of the montmorillonite is 200 nm.

3. The method for preparing the durable anti-mildew beauty glue with added reactive anti-mildew agent according to claim 1, characterized in that: In the primary modification, the particle size of the fumed silica is 40 nm.

4. The method for preparing the durable anti-mildew beauty glue with added reactive anti-mildew agent according to claim 1, characterized in that: In the mixture, the viscosity of the α,ω-dihydroxy polydimethylsiloxane at 25° C. is 80000 mPa·s; The particle size of the fumed silica is 40 nm; The viscosity of the dimethyl silicone oil at 25° C. is 500 mPa·s.

5. A durable anti-mildew cosmetic glue added with a reactive anti-mildew agent prepared by the preparation method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Epoxy resin self-flowing floating color sand wood color floor paint

    CN111484789A

  • Composite mildew-proof agent, preparation method thereof and mildew-proof organic silicon sealant

    CN115299460A